GAMBARAN SELF CONCEPT SISWA YANG MENGALAMI KECANDUAN MEROKOK - Maulidya Nurul Fajrin; Heris Hendriana; Devy Sekar Ayu Ningrum (IKIP Siliwangi, 2020)
The purpose of this study was to determine how the self-concept of students who experience smoking addiction. The method used in this research is a qualitative method with descriptive research type. The data collection techniques used were observation, interviews. The results of the study revealed that students' self-concept of smoking arose because of the results of their interactions with the environment, where smoking among their fellow students was considered normal and even considered a stylish and cool thing, so they thought smoking was not a wrong thing. Keywords: : self concept, smoking behavior.